Efficacy of thunder-fire moxibustion for cancer-related fatigue in breast cancer survivors: study protocol for a randomized controlled trial - Huakang Li; Huakang Li; Zhonglin Zhang; Qiang Li; Yuyang Jin; Yunjing Jia; Pengxuan Gu; Qi Xiao; Lingna Jin; Ziliang Wu; Bing Lin; Shanshan Wei; et al. (Frontiers in Oncology)
BackgroundCancer-related fatigue (CRF) is one of the most prevalent and debilitating symptoms experienced by breast cancer survivors, often associated with dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis. In China, moxibustion is widely used as a therapeutic approach for managing fatigue. Thunder-fire moxibustion (TFM), a novel technique with high thermal radiation and strong penetrative properties, may provide benefits for CRF. This study aims to assess the efficacy, safety, and underlying mechanisms of TFM in the treatment of CRF among breast cancer survivors.MethodsThis prospective, single-center, open-label, randomized controlled trial will recruit 70 breast cancer survivors diagnosed with CRF. Participants will be randomly assigned in a 1:1 ratio to either a waitlist control group or a TFM intervention group. All participants will receive standard care during the 30-day treatment period. Those in the TFM group will additionally undergo TFM treatment every other day, totaling 15 sessions. The primary outcome measure is the change in total fatigue score, assessed using the Piper Fatigue Scale, from baseline to the end of treatment. Additionally, this study will investigate the underlying mechanisms of TFM by evaluating changes in HPA axis-related hormone levels, inflammatory markers, gut microbiota composition, and conducting metabolomic analyses of fecal and blood samples.DiscussionThis study takes a multidisciplinary approach to comprehensively explore how TFM modulates biological systems involved in CRF, aiming to generate robust evidence. If successful, this study will provide high-quality, evidence-based reference points for the treatment of CRF in breast cancer survivors and inform future research in integrative medicine.Trial registrationThe study has been registered with the International Traditional Medicine Clinical Trial Registry (http://itmctr.ccebtcm.org.cn, ITMCTR2024000406).